Bacteria-derived chimeric toxins as potential anticancer agents - Khoshnood, Saeed; Fathizadeh, Hadis; Neamati, Foroogh; Negahdari, Babak; Baindara, Piyush; Abdullah, Mohd Azmuddin; Haddadi, Mohammad Hossein (Frontiers in Oncology, 2022)
Cancer is one of the major cause of death globally that the development of novel, specific, effective, and safe treatment strategies, are always pertinent. Despite great advances in recent years, chemotherapy as the primary treatment for cancer, still faces the limitations such as the lack of specificity, drug resistance, and treatment failure. Bacterial toxins have great potentials to be developed as anti-cancer agents and could boost the effectiveness of cancer chemotherapeutics. Bacterial toxins exert anti-cancer effects by affecting the cell cycle, apoptotic pathways, and regulating tumorigenesis. Chimeric toxins, which are the recombinant derivatives of the bacterial toxins, have been developed to address the low specificity of the conventional ones. Due to their targeting moieties, chimeric toxins can specifically and effectively detect and kill cancer cells. This review takes a comprehensive outlook at the anti-cancer properties of bacterial-derived toxins and discusses their practicality as therapeutic option in an integrative cancer treatment.